From transformation to chronification of migraine: pathophysiological and clinical aspects - Marta Torres‐Ferrús; Fabiana Ursitti; Alicia Alpuente; Francesco Brunello; Dario Chiappino; Tessa de Vries; Salvatore Di Marco; Salvatore Ferlisi; Ludovica Guerritore; N. González-García; Alicia González‐Martínez; D. Khutorov; et al. (2020)
Chronic migraine is a neurological disorder characterized by 15 or more headache days per month of which at least 8 days show typical migraine features. The process that describes the development from episodic migraine into chronic migraine is commonly referred to as migraine transformation or chronification. Ample studies have attempted to identify factors associated with migraine transformation from different perspectives. Understanding CM as a pathological brain state with trigeminovascular participation where biological changes occur, we have completed a comprehensive review on the clinical, epidemiological, genetic, molecular, structural, functional, physiological and preclinical evidence available.